Aplikasi Material Requirement Planning Mempertimbangkan Waktu Pemesanan Bahan Baku - Rizki Herdiyanto; Irna Yuniar; Renny Sukawati (@is The Best : Accounting Information Systems and Information Technology Business Enterprise, 2019)
In manufacturing companies, raw material requirements and production scheduling are preferred. Ordering by pemesans is the company's benchmark in determining production needs. So far, the company has not yet determined the material requirements to be used which make an estimate of the build-up material and the unavailability of materials in the warehouse that make the production process hampered. With the unavailability of materials in the warehouse, companies need to buy materials to support the production process, there are still many manufacturing companies that have not agreed on the length of the lead time for materials to warehouses which makes the production process hampered and unpredictable at any time. To overcome this problem, a web-based application can be made that can plan material procurement planning, production scheduling that addresses the matter of ordering raw materials using the Material Requirement Planning (MRP) method. The development process uses a prototype method (prototyping model). table of Main Production Schedules (MPS), Material Requirements Planning (MRP) tables, and produce purchase reports and purchase reports. Making applications using Codeigniter Framework programming language with Hypertext Preprocessor (PHP) script language.